A Comprehensive Analysis on the Regulatory Network Underlying Callus Induction and Adventitious Organogenesis Process in Stem of Populus Alba L - Li, Xiao-Yuan; Liu, Gui-Feng; Zeng, Qing-Yin; Liu, Yan-Jing (International journal of molecular sciences, 2025)
Populus species are important resources for ecological conservation and certain industry productions, and are also considered model tree species for scientific research. For tree species, in vitro plant regeneration is an important method of propagation due to the advantage of high multiplication rate. Although many molecular determinants for poplar regeneration have been investigated, the complete regulatory hierarchy network remains unclear. In this study, we tracked the temporal changes of endogenous hormone contents, physiological characteristics and transcriptional profiles during callus induction and adventitious organogenesis in a stem of Populus alba L. to explore the regulatory dynamics of in vitro regeneration in poplars. The results imply that auxin may promote the formation of callus in P. alba by activating the expression of WOX11/12. By up-regulating the expression of CUC1/2, the development of callus begins to initiate apical meristem (SAM) at day 12. The cytokinin-mediated pathway regulates the adventitious shoot formation by ESR1 and WUS. The precursors of active gibberellin GA1, GA53 and GA19 were accumulated in the early stage of callus induction, and then they continued to decrease. JA may function on adventitious shoot regeneration due to its accumulation after 12 days of induction. The dominant hormonal components and regulatory factors during regeneration were identified. Based on the results, a regeneration pathway regulated by auxin and cytokinin for poplars is proposed. The key regulators identified in this study will accelerate the exploration and understanding of the asexual reproduction mechanism of poplar trees.